Identidade e mundialização na Igreja Universal do Reino de Deus: estratégias para entrar na modernidade - Costa Neto, Moisés (2009)
This work aims to show the growth strategies of the Universal Church of the Kingdom of God as well as cultural hybridization processes that lead to adapt to different cultures and socioeconomic backgrounds. Also addresses the ritualistic processes that promote the construction of a typical Pentecostal identity and their way of being in the world, specifically their sense of work and vocation, in Weberian terms, which lead them to increase the faithful quota year after year. This said "way of being" brings the peculiarity of inserting the individual as part of the world and, even more, its transformer, contradicting thus the historical perspective of evangelical denominations that precede it.